Worker mobility, displacement, redeployment and wage dynamics in Italy - Bruno Contini; Claudia Villosio (Institute for the Study of Labor (IZA), 2007)
We investigate various stylized facts on wage growth, labor mobility and firm size, to date unexplored in Italy. Using a wage decomposition that allows to separate individual premiums from firm-effects, we ascertain: (1) whether movers are better off than stayers; (2) whether firm size affects the outcome of workers' mobility across; and (3) the extent to which did job displacement and redeployment inflict wage losses to downsized workers. The sample - a closed panel of full-time male employees, aged 20-50, at work from 1986 to 1991 - is drawn from the employer-employee linked database WHIP (Work Histories Italian Panel)
urn:nbn:de:101:1-20080416421
Keywords: 330; Lohn; Arbeitsmobilität; Lohnstruktur; Betriebsgröße; Italien